The Influence of Discount and Social Proof Programs in Determining Decisions to Buy Goods on Tiktok Shop in Pekanbaru City - Linofal Fakhrin; Adinda Triandini; Lifatin Nada; Alfin Fuji Hidayati; Mohammad Amin (Cv. Syntax Corporation Indonesia, 2026)
The development of digital technology and the increasing use of social media have encouraged the emergence of the social commerce phenomenon, one example of which is the TikTok Shop platform, which integrates entertainment activities, social interactions, and buying and selling transactions within a single application. TikTok Shop offers various marketing strategies to influence consumer behavior, including discount programs and social proof. Discount programs provide economic incentives in the form of price reductions, vouchers, and limited-time promotions, while social proof refers to social validation mechanisms, such as customer reviews, ratings, sales numbers, and user recommendations, that can increase consumer trust. This study aims to analyze the influence of discount and social proof programs on consumer purchase decisions at TikTok Shop in Pekanbaru City. The research employs a quantitative method with an associative approach. Primary data were obtained through questionnaires distributed to 30 respondents selected using a purposive sampling technique. Data analysis was conducted through validity and reliability tests, classical assumption tests, and multiple linear regression analysis to examine the partial and simultaneous effects of the variables. The results showed that discount programs had a positive and significant effect on purchase decisions, whereas social proof did not have a partially significant effect. However, simultaneously, both variables had a significant effect on purchase decisions. The coefficient of determination (R²) value of 41.3% indicates that purchase decisions can be explained by discount and social proof programs, while the remaining 58.7% are influenced by factors outside the research model. These findings indicate that price-related factors are the primary considerations for consumers when shopping through TikTok Shop. This research is expected to provide a theoretical contribution to the development of digital marketing studies and serve as a practical recommendation for business actors in designing more effective promotional strategies.